2018
DOI: 10.1007/s10909-018-2105-y
|View full text |Cite
|
Sign up to set email alerts
|

Collective Excitations in Bose–Fermi Mixtures

Abstract: We investigate collective excitations of density fluctuations and a dynamic density structure factor in a mixture of Bose and Fermi gases in a normal phase. With decreasing temperature, we find that the frequency of the collective excitation deviates from that of the hydrodynamic sound mode. Even at a temperature much lower than the Fermi temperature, the collective mode frequency does not reach the collisionless limit analogous to zero sound in a Fermi gas, because of collisions between bosons and fermions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…These distinct quantum statistical properties may give rise to an interesting feature of collective modes. The earlier study showed that there surprisingly exists a long-lived sound mode between the hydrodynamic regime and the collisionless regime [23]; this is in contrast to our general knowledge, where a lifetime of the collective mode is very short in the crossover regime.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…These distinct quantum statistical properties may give rise to an interesting feature of collective modes. The earlier study showed that there surprisingly exists a long-lived sound mode between the hydrodynamic regime and the collisionless regime [23]; this is in contrast to our general knowledge, where a lifetime of the collective mode is very short in the crossover regime.…”
Section: Introductionmentioning
confidence: 66%
“…In an earlier study [23], we examined a collective sound mode in a normal phase of a uniform Bose-Fermi mixture, composed of single-species bosons and single-species fermions interacting via s-wave scatterings, where collisions between fermions are absent because of the Pauliblocking. The intraspecies (Bose-Bose) scattering becomes important at low temperature close to the BEC transition temperature because of Bose-enhancement, which may lead to the hydrodynamic regime.…”
Section: Introductionmentioning
confidence: 99%
“…These competitive quantum statistical properties may give rise to an interesting property of collective modes. In fact, in the case of a spatial uniform system, there exists a long-lived sound mode in the crossover region between collisionless and hydrodynamic regimes [10]. In this paper, considering the familiar experimental situation in ultracold atomic gases, we study dipole modes in a Bose-Fermi mixture for exploring exotic collective mode.…”
Section: Introductionmentioning
confidence: 99%